Penerapan Sistem Kearsipan untuk Meningkatkan Efektivitas Pengelolaan Dokumen pada Lingkungan Perkantoran Notaris/PPAT - Tyas, Naysilla Ika Yuli Setyaning (Maliki Interdisciplinary Journal, 2026)
Unstructured archive management remains a common problem in notary and Land Deed Official (PPAT) offices, particularly related to the accumulation of old and new documents without clear classification. This condition affects the effectiveness of document management and causes delays in retrieving important files such as deeds and certificates. This article aims to describe the implementation of an archival system to improve document management effectiveness in notary/PPAT office environments. This study employs a qualitative descriptive approach based on six months of Field Work Practice (PKL). Data were collected through direct observation of filing, storage, and document retrieval processes. The findings indicate that prior to the implementation of an archival system, documents were managed conventionally without classification by year or document type, resulting in prolonged retrieval times that could take hours or even days. The implementation of a structured archival system through document classification, labeling, and separation of active and inactive archives improved the organization of records and significantly reduced retrieval time. In conclusion, the application of a systematic archival system enhances work effectiveness and supports better administrative services in notary/PPAT offices.